Contrasting Market Dynamics: The Fama-French Model in the SET and MAI of Thailand - Kitkanasiri, Chavalit; Palahan, Sirinda; Pan-urai, Jarukorn (Journal of Applied Economics and Management Strategy, 2025)
This paper examines the applicability of the Fama-French three-factor model to the equity markets in Thailand, namely the SET and the MAI. Using a sample of data spanning 2012, to 2021, this study analyzes whether the factors of the model describe efficiently the stock returns in these markets and if the results are consistent with Fama and French (1993), in which small stocks outperform big stocks and value stocks outperform growth stocks. The results confirm that the Fama-French model holds in both the SET and the MAI, as size and book-to-market ratios exhibit significant explanatory power on stock returns. However, in the MAI, the size and value factors have negative signs, diverging from the original model’s predictions. These findings have practical implications for portfolio managers. While size and book-to-market ratios are significant in both markets, managers in the MAI might benefit by allocating more capital to growth stocks and increasing their exposure to large-cap stocks in order to enhance portfolio returns. Yet, this strategy needs a more refined understanding of risks in investing in growth and large-cap equities since these results are contrary to the Fama and French (1993)’s hypothesis. By comparing and differentiating between SET and MAI, this study adds to existing literature with recent evidence on the effectiveness of the Fama and French (1993) model in Thailand and provides useful guidelines for portfolio management under these specific market settings.